OS DESAFIOS DA LIDERANÇA: COMO ATINGIR RESULTADOS SIGNIFICATIVOS - da Silva Santos do Nascimento, Monique; Alves da Costa, Tatiana; Cabral Azevedo, Jefferson (LINKSCIENCEPLACE, 2026)
This article is premised verify the issues of leadership and its challenges, an issue that currently is evident because of its relevance to the organization. This text addresses several questions on the subject citing some essential concepts for building skills and competencies for the formation of a good leader. In this work there are the tools used to achieve the desired results and overcome organizational conflicts Highlights the importance of employees as thrusts of every enterprise without which all systems would no longer make sense, it will show the importance of motivation and power that a leader has on its employees. The theoretical basis authors were used as (CHIAVENATO, 2003; MAXIMIANO, 2007; Dancini, 2012) corroborate that in order to achieve meaningful results, it is necessary that the individual feel motivated and realize the opportunities that are around you.